Metode dakwah da’i perbatasan dalam mengatasi kenakalan remaja - Adi Saleh (Educenter : Jurnal Ilmiah Pendidikan, 2022)
Adolescents with the problems they face need serious attention from various parties, because adolescence is part of a typical stage of life. This stage also makes adolescents occupy a position that tends to be dilemmatic and unstable in responding to every life problem they face. One of them is juvenile delinquency displayed by teenagers in Simeulue Regency. Therefore, the role of da'i dakwah on the border assigned by the Aceh Islamic Sharia Office to the Simeulue Regency area to overcome juvenile delinquency is very necessary. Data mining in this study uses observation, in-depth interviews and documentation methods. After conducting the research, the most important findings of this study can be formulated as follows: Broadly speaking, the forms of juvenile delinquency that exist in Simeulue Regency include; promiscuity, drugs, theft, motorcycle gangs. The factors that cause juvenile delinquency in Simeulue Regency include; family factors, environmental factors, peer factors, following factors and lack of supervision from the government. While the da'i border da'i da'wah method in overcoming juvenile delinquency in Simeulue Regency is divided into three; First, the Al-Hikmah da'wah method is conveyed in the da'wah model of lectures, exemplary, bil hal and tadabbur nature. Second, the Al-Mujadalah Bi-al-Lati Hiya Ahsan da'wah method is conveyed in the discussion da'wah model. Third, the method of preaching Al-Mau'idza Al-Hasanah.